Physical properties of dental plaster filled with marble powder: a pilot study - Elshereksi, Nidal; Alshabah, Bushra L; Abouod, Nadine M; Albahloul, Retaj K (International Journal of Dental Materials, 2022)
Background: Gypsum materials are frequently utilized in dental technology. Dental plaster is one of these products that is mainly used to produce dental casts and mounting purposes. Although the cost of dental plaster is very low, their inferior compressive strength, low abrasion resistance and dimensional instability restricted their usage as primary and working casts. The inclusion of different fillers in gypsum products could play an important role in improving their performance.Aim: The aim of this study was to evaluate the physical properties of dental plaster incorporated with various concentrations of Marble powder (MP).Methodology: Gypsum composites were prepared by incorporating 1.0, 3.0, 6.0 and 9.0 wt.% of MP. The neat plaster/mixture comprised the control group. The prepared gypsum composites samples were characterized in comparison with the control group. The density, porosity and fluidity of dental MP/plaster samples were investigated. The correlation between density and fluidity was also conducted.Results: The gypsum composite samples displayed a higher density of 47% than the control group. However, a remarkable decrease in porosity level was observed as MP content increased. Significant improvements in the fluidity of the dental plaster after impregnating MP filler (p0.05).Conclusion: The concentration of MP in dental plaster is proportional to the density and fluidity of the material and inversely proportional to its porosity.